Efficient Engineering Techniques for Segregation and Management of Non-Biodegradable Wastes: Saving the Earth by Replenishing its Dearth - Poddar, Tamojit; De, Nirnimesh; Sarkar, Sagnik (International Journal of Sustainable Energy and Environmental Research, 2020)
The climatic conditions of the Earth seem to be deteriorating every single moment and mankind is receiving the signals of an upcoming environmental catastrophe in the forms of Global Warming, Ozone holes and Environmental Pollution. The Segregation and Management of wastes are two vital issues in the 21st century globalized world. The waste generation rates are on a sharp rise throughout the world. In 2016, the quantity of solid wastes generated globally summed up to a figure of 6.3 billion metric tonnes. With a swift population growth and rapid urbanization, scientists are expecting a rise of about 70% in the production of wastes as compared to 2016 amounting to nearly 26 billion metric tonnes of in 2050. Plastics, MPW etc. constitute a major portion of these wastes having secured an irreplaceable role in human life today. This paper majorly gives an insight to the Recycling of the globally produced wastes (after their Segregation by an IoT/GLCM/PLC based Segregator) by utilizing them in Road/ Pavement Construction, RDF, Mortar Aggregates and Toilet Blocks (Plastones) in some innovative, cost-efficient and easy-to-implement novel methods viz. Cold Plasma Pyrolysis, CMP, Injection Molding etc. for the Management of wastes to frame a greener and sustainable future. Also, certain high potential techniques for the Re-usage and Reduction of waste products have been incorporated for the Environmental amelioration.